A case of immune thrombocytopenia due to miliary tuberculosis effectively treated with eltrombopag. (2020) - Wada, Hiroshi; Sakashita, Takuto
Abstract: An 80-year-old woman was diagnosed with miliary tuberculosis. Laboratory findings showed marked thrombocytopenia (3000/μl). Immune thrombocytopenia (ITP) was diagnosed because platelet transfusion was ineffective, and bone marrow puncture demonstrated a normal number of megakaryocytes. Anti-tuberculosis treatment was started promptly, followed by prednisolone 20 mg. However, the platelet count did not increase. The effect of high-dose intravenous immunoglobulin was temporary. She was not responded to prednisolone, and eltrombopag 12.5 mg was added. The eltrombopag dose was increased by 12.5 mg every two weeks. When the eltrombopag dose reached 50 mg, the thrombocytopenia improved sufficiently (44, 000/μl). She didn't have any severe bleeding and thrombotic complications. The treatment of tuberculosis went well and there was no side effect of anti-tuberculosis treatment. Eltrombopag can be a useful treatment for ITP due to tuberculosis.